2002
DOI: 10.1126/science.1075664
|View full text |Cite
|
Sign up to set email alerts
|

Avian Persistence in Fragmented Rainforest

Abstract: What factors determine the persistence of species in fragmented habitats? To address this question, we studied the relative impacts of forest deterioration and fragmentation on bird species in 12 rainforest fragments in Kenya, combining 6 years of individual capture-recapture data with measurements of current captures and museum specimens. Species mobility, as estimated from species-specific dispersal rates, and tolerance to habitat deterioration, as estimated from change in fluctuating asymmetry with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
190
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(200 citation statements)
references
References 16 publications
5
190
2
3
Order By: Relevance
“…6) provided by corridors (7)(8)(9)(10), but this has been difficult to achieve for small species, like birds, that move at landscape scales (6). More specific movement information from free-ranging animals is especially important for forest specialists, particularly understory insectivores, because this group appears to be most sensitive to the isolation effects of fragmentation (4,11,12). Both forested corridors and fencerows of individual, living trees have been promoted as landscape elements to facilitate the movement of birds and other forest dependent animals (11,13), but no studies of birds have directly measured movement in these habitats.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6) provided by corridors (7)(8)(9)(10), but this has been difficult to achieve for small species, like birds, that move at landscape scales (6). More specific movement information from free-ranging animals is especially important for forest specialists, particularly understory insectivores, because this group appears to be most sensitive to the isolation effects of fragmentation (4,11,12). Both forested corridors and fencerows of individual, living trees have been promoted as landscape elements to facilitate the movement of birds and other forest dependent animals (11,13), but no studies of birds have directly measured movement in these habitats.…”
mentioning
confidence: 99%
“…2), corridors have been widely advocated as a means to maintain biodiversity and ecological processes in fragmented landscapes (3,4). Several studies have demonstrated that target organisms occur in corridors (5), providing indirect evidence that they facilitate movement.…”
mentioning
confidence: 99%
“…The highest distance between two forest patches was 920 meters ( Table 2), so that might be the reason why significant difference statistically was not found. Also the species has high mobility and the corridors observed in this study make it likely to survive in fragmented landscapes with low isolation distance (Lens et al, 2002;Thomas, 2000). Their densities decreased with an increase in isolation distance (Figure 2).…”
Section: Discussionmentioning
confidence: 90%
“…Lens et al (2002) found that bird occupancy in a forest patch increased with mobility and the tolerance to deterioration of the habitat.…”
mentioning
confidence: 99%
“…There are discoveries made on biological diversity for small mammals [4][5][6][7], larger mammals such as primates [8], carnivores [9], invertebrates [10], reptiles and amphibians [11], and birds [12][13][14]. The literature also indicates rich diversity of plants like angiosperms [15,16].…”
Section: Introductionmentioning
confidence: 99%